Endovascular treatment of acute ischemic stroke with a fully radiopaque retriever: A randomized controlled trial - Zhang, Yongxin; Liu, Pei; Li, Zifu; Peng, Ya; Chen, Wenhuo; Zhang, Liyong; Chu, Jianfeng; Kuai, Dong; Chen, Zhen; Wu, Wei; Xu, Yun; Zhang, Yong; et al. (Frontiers in Neurology, 2022)
Purpose A randomized controlled non-inferiority trial was conducted to compare the Neurohawk and the Solitaire FR in terms of safety and efficacy. A sub-analysis was performed to evaluate the efficacy and safety of endovascular treatment in acute ischemic stroke (AIS) caused by intracranial atherosclerotic disease (ICAD) larger vessel occlusion (LVO). Methods AIS patients with LVO in the anterior circulation were randomly assigned to two group. The primary efficacy endpoint was successful reperfusion (mTICI 2b-3) rate by the allocated retriever (non-inferiority margin of 12.5%). Safety outcomes were symptomatic intracranial hemorrhage (sICH) and all-cause mortality within 90 days. In subgroup analysis, the patients were divided into the ICAD group and non-ICAD group, and baseline characteristics, angiographic and clinical outcomes were compared. Results A total of 232 patients were involved in this analysis (115 in the Neurohawk group and 117 in the Solitaire group). The rates of successful reperfusion of the Neurohawk group was non-inferior to the Solitaire group (88.7% vs 90.6%; 95%CI of the difference, -9.74%~5.94%; p=0.867). The rate of sICH and all-cause mortality were comparable in two groups. In subgroup analysis, there were 58 patients in the ICAD group and 174 patients in the non-ICAD group. The final successful reperfusion rates showed comparable in two groups. Mortality within 90 days was relatively lower in the ICAD group (6.90% vs. 17.24%; p=0.054). Conclusion The Neurohawk retriever is non-inferior to the Solitaire FR. The sub-analysis suggested that endovascular treatment is effective and safe in AIS patients with ICAD-LVO.